2009
DOI: 10.1530/eje-09-0287
|View full text |Cite
|
Sign up to set email alerts
|

Safety aspects of GH replacement

Abstract: In adults, GH replacement therapy will often be maintained for decades. Owing to the long duration of GH replacement in many adults, it is essential to establish the long-term safety aspects of the treatment. In this review, studies that have investigated the safety profile of long-term GH replacement will be reviewed with an emphasis on studies based on data from the Pfizer International Metabolic Database (KIMS). These studies show that long-term GH replacement in adults is safe and that long-term GH replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 97 publications
1
23
0
5
Order By: Relevance
“…572 Dyslipidemia and metabolic syndrome are more likely to occur in individuals with GH deficiency, but individuals with chronic heart failure are also generally resistant to GH. Although there is no evidence that GH deficiency itself causes substantial clinical cardiac dysfunction in childhood cancer survivors specifically, numerous studies of adults with chronic heart failure have shown that the GH-insulin-like growth factor-1 axis activity in this condition is reduced.…”
Section: Gh Deficiencymentioning
confidence: 99%
“…572 Dyslipidemia and metabolic syndrome are more likely to occur in individuals with GH deficiency, but individuals with chronic heart failure are also generally resistant to GH. Although there is no evidence that GH deficiency itself causes substantial clinical cardiac dysfunction in childhood cancer survivors specifically, numerous studies of adults with chronic heart failure have shown that the GH-insulin-like growth factor-1 axis activity in this condition is reduced.…”
Section: Gh Deficiencymentioning
confidence: 99%
“…This is most likely due to the insulin antagonistic eff ects of GH, which is characterized by increasing hepatic gluconeogenesis and glycogenolysis with decreasing peripheral glucose utilization [ 31 ] . Although long-term studies have shown no evidence that patients with growth hormone defi ciency and normal BMI have an increased risk of developing DM after rhGH treatment, the risk of developing DM in subjects with high BMI receiving rhGH treatment, such as the obese subjects enrolled in this study, should be further evaluated in long term studies [ 32 ] . This study has a limitation of a lack of placebo arm.…”
Section: Discussion ▼mentioning
confidence: 97%
“…Only six new cases of diabetes mellitus were diagnosed during the treatment period. Although there are few data, there is no evidence that GH replacement therapy increases the risk of diabetes mellitus in adults with GHD [25,55,56]. Svensson and colleagues [21] suggest that fasting blood glucose develop similarly in GHD patients as in healthy control subjects due to normal aging.…”
Section: Anthropometric and Metabolic Changesmentioning
confidence: 99%